Effect of Hydroxy Propyl Cellulose, Polyethylene Glycol, Carboxy Methyl Cellulose and Polyvinyl Pyrrolidone on the Microstructure and Photocatalytic Activity of Nd-TiO2/SiO2 Films under Visible Light Irradiation - Samadi, Susan (Asian Journal of Chemistry, 2012)
Nd-TiO2/SiO2 films were prepared separately by the sol-gel method with the addition of polyethylene glycol (PEG 2000), hydroxy propyl cellulose, carboxy methyl cellulose and polyvinyl pyrrolidone as dispersions. The porous Nd-TiO2/SiO2 was obtained after heat treatment for 2 h at 500 ºC in air, with the surface area up to 331.76 m2 g-1, which measured using the Brunauer- Emmett-Teller method. Scanning electron microscopy showed that the particle size of Nd-TiO2/SiO2 with hydroxy propyl cellulose is smaller than the others and the microstructure of the film became loose with the addition of carboxy methyl cellulose. The influence of dispersions on the phase transformation of Nd-TiO2/SiO2 from amorphous to anatase was investigated by using X-ray diffraction. The sample structures were characterized by infrared spectroscopy. Subsequently, the photocatalytic activity of Nd-TiO2/SiO2 film under visible light irradiation would be enhanced by polyvinyl pyrrolidone, carboxy methyl cellulose and polyethylene glycol as dispersions.